SSB recruitment of Exonuclease I aborts template-switching in Escherichia coli - Laranjo, Laura T. (DNA Repair (Amst), 2017)
Misalignment of a nascent strand and the use of an alternative template during DNA replication, a process termed “template-switching”, can give rise to frequent mutations and genetic rearrangements. Mutational hotspots are frequently found associated with imperfect inverted repeats (“quasipalindromes” or “QPs”) in many organisms, including bacteriophage, bacteria, yeast and mammals. Evidence suggests that QPs mutate by a replication template-switch whereby one copy of the inverted repeat templates synthesis of the other. To study quasipalindrome-associated mutagenesis (“QPM”) more systematically, we have engineered mutational reporters in the lacZ gene of Escherichia coli, that revert to Lac(+) specifically by QPM. We and others have shown that QPM is more efficient during replication of the leading strand than it is on the lagging strand. We have previously shown that QPM is elevated and that the leading-strand bias is lost in mutants lacking the major 3′ ssDNA exonucleases, ExoI and ExoVII. This suggests that one or both of these exonucleases more efficiently abort template-switches on the lagging strand. Here, we show that ExoI is primarily responsible for this bias and that its ability to be recruited by single-strand DNA binding protein plays a critical role in QPM avoidance and strand bias. In addition to these stand-alone exonucleases, loss of the 3′ proofreading exonuclease activity of the replicative DNA polymerase III also greatly elevates QPM. This may be because template-switching is initiated by base misincorporation, leading to polymerase dissociation and subsequent nascent strand misalignment; alternatively or additionally, the proofreading exonuclease may scavenge displaced 3′ DNA that would otherwise be free to misalign.